Trunnion Structure Analysis with Rigging Variations at The Loadout Stage During Lifting Jacket Platform Process - Muhammad Faris Pramudiansyah; Yoyok Setyo Hadiwidodo; Handayanu (Department of Ocean Engineering, 2025)
An offshore structure is a structure that is operated at an offshore base and has the general function of oil and gas exploitation and exploration. The making process of this structure is called the fabrication process. Fabrication is the process which is covered the whole activities to produce the structure. Lifting is a process that is included in this fabrication step.Many important lifting items correspond to the requirement to let the lifting process is working. A trunnion is a tubular member that helps lift the structure because it is where slings can be convoluted. Trunnion can be called lifting lugs, depending on the engineer at the company used.In this research, the trunnion that must be analyzed is the trunnion that has the general function for the jacket-to-lifting processes. In contrast, the researcher analyzed the effect of various rigging configurations. The considered variable of rigging configuration is the shape and amount of the spreader bar.